Improved DNA equilibrium binding affinity determinations of platinum(ii) complexes using synchrotron radiation circular dichroism1. Issue 12 (21st June 2015) - Ang, Dale L.; Jones, Nykola C.; Stootman, Frank; Ghadirian, Bahman; Aldrich-Wright, Janice R.
<x xml:space="preserve">Abstract</x> The DNA binding affinity of a range of Pt(ii) complexes was reinvestigated using SRCD and a new method was implemented for determining the binding constant, saving time and minimising data collection.